Close the gap for vision: The key is to invest on coordination. (December 2013) - Hsueh, Ya‐seng (Arthur); Dunt, David; Anjou, Mitchell D; Boudville, Andrea; Taylor, Hugh
Abstract Objective The study aims to estimate costs required for coordination and case management activities support access to treatment for the three most common eye conditions among Indigenous Australians, cataract, refractive error and diabetic retinopathy. Design Coordination activities were identified using in‐depth interviews, focus groups and face‐to‐face consultations. Data were collected at 21 sites across Australia. The estimation of costs used salary data from relevant government websites and was organised by diagnosis and type of coordination activity. Setting Urban and remote regions of Australia. Interventions Needs‐based provision support services to facilitate access to eye care for cataract, refractive error and diabetic retinopathy to Indigenous Australians. Main outcome measures Cost (AUD in 2011) of equivalent full time (EFT) coordination staff. Results The annual coordination workforce required for the three eye conditions was 8.3 EFT staff per 10 000 Indigenous Australians. The annual cost of eye care coordination workforce is estimated to be AUD21 337 012 in 2011. Conclusions This innovative, 'activity‐based' model identified the workforce required to support the provision of eye care for Indigenous Australians and estimated their costs. The findings are of clear value to government funders and other decision makers. The model can potentially be used to estimate staffing and associated costs for other Indigenous and non‐Indigenous health needs.